Quantifying and monitoring fibrosis in non-alcoholic fatty liver disease using dual-photon microscopy. Issue 6 (28th September 2019) - Wang, Yan; Wong, Grace Lai-Hung; He, Fang-Ping; Sun, Jian; Chan, Anthony Wing-Hung; Yang, Jinlian; Shu, Sally She-Ting; Liang, Xieer; Tse, Yee Kit; Fan, Xiao-Tang; Hou, Jinlin; Chan, Henry Lik-Yuen; et al.
Abstract : Objective: Fibrosis stage is strongly associated with liver-related outcomes and is a key surrogate endpoint in drug trials for non-alcoholic steatohepatitis. Dual-photon microscopy allows automated quantification of fibrosis-related parameters (q-FPs) and may facilitate large-scale histological studies. We aim to validate the performance of q-FPs in a large histological cohort. Design: 344 patients with non-alcoholic fatty liver disease (NAFLD) underwent 428 liver biopsies (240 had paired transient elastography examination). Fibrosis stage was scored using the NASH Clinical Research Network system, and q-FPs were measured by dual-photon microscopy using unstained slides. Patients were randomly assigned to the training and validation cohorts to test the performance of individual q-FPs and derive optimal cut-offs. Results: Over 25 q-FPs had area under the receiver-operating characteristics curves >0.90 for different fibrosis stages. Among them, the perimeter of collagen fibres and number of long collagen fibres had the highest accuracy. At the best cut-offs, the two q-FPs had 88.3%–96.2% sensitivity and 78.1%–91.1% specificity for different fibrosis stages in the validation cohort. q-FPs and histological scoring had nearly identical correlations with liver stiffness measurement, suggesting that the accuracy of q-FPs approached that of histological assessment. Among patients with paired liver biopsies, changes in the same q-FPs were associated with changes in fibrosis stage. At a median follow-up of 5.6 years, baseline q-FPs predicted liver-related events. Conclusion: q-FP is highly accurate in the assessment of fibrosis in NAFLD patients. This automated platform can be used in future studies as objective and reliable evaluation of histological fibrosis.